ALIH AKSARA DAN ALIH BAHASA TEKS SEJARAH RINGKAS SYEKH MUHAMMAD NASIR (SYEKH SURAU BARU) OLEH IMAM MAULANA ABDUL MANAF AMIN - Honesti, Honesti; Nasution, Bakhtarudin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
This article was written to (1) describing a short history text of Syekh Muhammad Nasir (Syekh Surau Baru) by Imam Maulana Abdul Manaf Amin; (2) presenting the edition of short history text of Syekh Muhammad Nasir (Syekh Surau Baru) by Imam Maulana Abdul Manaf Amin; (3) presenting the tranlation of short history text of Syekh Muhammad Nasir (Syekh Surau Baru) by Imam Maulana Abdul Manaf Amin. The purpose of this research was the story about short history of Syekh Muhammad Nasir (Syekh Surau Baru) by Imam Maulana Abdul Manaf Amin. There were four procedures of this research, data collection, manuscript description, script switching, and translation. The result of this research is available in the form of text about short history text of Syekh Muhammad Nasir (Syekh Surau Baru) by Imam Maulana Abdul Manaf Amin in Latin script and Indonesian language and there are also Minangkabau vocabularies.Keywords: philology, manuscript, transcription, transfer of language